The Billion-Dollar Question: Quantifying AI's Role in Reducing Medical Errors - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Billion-Dollar Question: Quantifying AI's Role in Reducing Medical Errors Medical errors represent a profound challenge to global healthcare systems...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Machine Learning